Comparing self-regulation strategies among adult learners from Poland, Serbia, Slovakia, and the Czech Republic - Vaculíková, Jitka (Frontiers in Psychology, 2024)
An active and constructive process whereby individuals possess the ability to develop, implement, and flexibly maintain planned behavior in order to achieve a desired achievement goal is referred to as self-regulation. The aim of the present study is to examine the factorial structure and psychometric properties of the Self-Regulation Questionnaire, validated in the Czech educational context (SRQ-CZ). The other target is to identify any usage of self-regulation strategies which may differ as nationality, gender, age, education, and internal motivation to learn come into play. A total of 1,711 adult learners from Poland, Serbia, Slovakia, and the Czech Republic who were enrolled in a formal secondary or higher education system pursuing professions in the field of humanities, social and health care sciences participated in this study. A measurement-invariant four-factor model was obtained across all countries (min. CFI, TLI = .918, and .902, max. RMSEA = .059; ω between 0.625 and 0.838, and Cronbach’s α between 0.622 and 0.837), including the Impulse Control, Goal Orientation, Self-Direction, and Decision Making subscales. Generally, the study confirmed a gradual increase in scores that measure positive self-regulatory qualities (Goal Orientation and Decision Making) and a decrease in unfavorable self-regulatory qualities (Impulse Control and Self-Direction) with higher age, education, and motivation, with no gender differences reported within countries. Moreover, scores on Goal Orientation and Decision Making dominated between countries. In conclusion, the SRQ-CZ demonstrated its suitability for cross-national comparisons, and personal characteristics appear to be important factors that distinguish those with high and low self-regulation.